Folding Fun Boosts Early Childhood Fine Motor Skills Globally: Keseruan Melipat Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Secara Global - Oktavia, Hanifa Prisma; Destiana, Evie (Indonesian Journal of Innovation Studies, 2024)
This study investigates the efficacy of folding activities to enhance fine motor skills in Group A children at RA An Nur Kedung Jumputrejo Sukodono Sidoarjo, utilizing Classroom Action Research (CAR) with the Kemmis and McTaggart models. Fourteen children (9 boys, 5 girls) participated in Pre Cycle, Cycle 1, and Cycle 2 interventions, with data collected via observation, documentation, and interviews. Results show a remarkable improvement from a baseline fine motor skill percentage of 35% in Pre Cycle to 95% in Cycle 2, surpassing the 75% success indicator. These findings underscore the effectiveness of folding activities in early childhood education and provide valuable insights for educators aiming to enhance motor skill development in young learners. Highlight: Improved fine motor skills through folding activities. Utilization of Classroom Action Research for systematic intervention. Valuable insights for educators enhancing motor skills in young learners. Keyword: Fine motor skills, Folding activities, Classroom Action Research, Early childhood education, Motor skill development